Who becomes a dermatologist? A repeated cross-sectional study on diversity in the Dutch dermatology workforce - Sheeney T. Magdalena; Angelo Li; Jim E. Zeegelaar; Lianne Mulder (PLoS ONE, 2026)
Background Workforce diversity in dermatology is crucial for equitable, high-quality care, given the impact of skin tone, culture, and socio-economic status on skin conditions. Although this has been studied in other countries, data on the demographic makeup of Dutch dermatologists is lacking. This study aims to assess workforce diversity in Dutch dermatology over time. Methods We conducted a nationwide repeated cross-sectional study using pseudonymized microdata from Statistics Netherlands, including sex, migration background, and parental socio-economic indicators. Descriptive statistics were used to track demographic trends between 2005 and 2023, and multivariable logistic regression analyses were performed to evaluate which variables influenced the odds that registered physicians in the 2023 national healthcare professional register (BIG register) had to be a dermatologist. Results Female representation rose from 35.4% in 2005 to 61.7% in 2023. In 2023, 84.4% of dermatologists had no migration background or a European migration background. Dermatologists with Turkish, Moroccan, Surinamese, or Caribbean Dutch origins were underrepresented. Despite a net increase of 289 dermatologists, only 56 of this net increase consisted of dermatologists with a non-European background. Multivariable regression analysis showed that being female (OR 1.609 [1.143–2.266]), having parents in the top 20% assets bracket (OR 2.251 [1.272–3.984]), or having physician parents (OR 1.326 [1.011–1.740]) were associated with higher odds of being a registered dermatologist among the younger generation of physicians. Conclusions The findings highlight a persistent lack of ethnic and socio-economic diversity in the Dutch dermatology workforce, despite broader demographic shifts in the general population and medical student cohorts. The underrepresentation of dermatologists with a migration background may have implications for equitable patient care, particularly in the context of cultural and linguistic barriers, as well as differences in disease presentation across skin tones. Further research is warranted to explore the potential impact of workforce diversity on patient outcomes.